(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The effect of foliar spray of young lemon trees (santa teriza) with boric acid (500- 1000 ppm), on antioxidant enzymes activities (peroxidas POD, poly phenol oxidase PPO ), total phenolic content, total chlorophyll and their influence on leaf miner ( Phyllocnistis citrella) activity ( tunnel length and damage density ) under field condition was investigated . The results showed that boron 1000 ppm enhanced POD activity (0.387 mm-l mg -l protein) and PPO activity (1.389 ΔA/min/g FW), and decreased total phenolic content (4.622 mg/g). Both boron concentration improved total leaf chlorophyll content ( spad29.07- 24.06). The results demonstrated as well that Boron treatment has a beneficial effect in reducing leaf miner activity, by decreasing tunnel length and damage density. Key words: Boron- Santa teriza lime- Antioxidant enzymes- Total phenolic content_ Total chlorophyll- Citrus leaf miner- Tunnel length- Damage density.